Identification and characterization of contrasting sunflower genotypes to early leaf senescence process combining molecular and physiological studies (Helianthus annuus L.) - López Gialdi, A.I.; Moschen, Sebastian Nicolas; Villán, C.S.; López Fernández, María Paula; Maldonado, Sara Beatriz; Paniego, Norma Beatriz; Heinz, Ruth Amelia; Fernandez, Paula Del Carmen (2017)
Leaf senescence is a complex mechanism ruled by multiple genetic and environmental variables that affect crop yields. It is the last stage in leaf development, is characterized by an active decline in photosynthetic rate, nutrients recycling and cell death. The aim of this work was to identify contrasting sunflower inbred lines differing in leaf senescence and to deepen the study of this process in sunflower. Ten sunflower genotypes, previously selected by physiological analysis from 150 inbred genotypes, were evaluated under field conditions through physiological, cytological and molecular analysis. The physiological measurement allowed the identification of two contrasting senescence inbred lines, R453 and B481-6, with an increase in yield in the senescence delayed genotype. These findings were confirmed by cytological and molecular analysis using TUNEL, genomic DNA gel electrophoresis, flow sorting and gene expression analysis by qPCR. These results allowed the selection of the two most promising contrasting genotypes, which enables future studies and the identification of new biomarkers associated to early senescence in sunflower. In addition, they allowed the tuning of cytological techniques for a non-model species and its integration with molecular variables